Analysis of the Restriction of Vancomycin Use in Hospitals Before, During and After the Implementation of the Antimicrobial Resistance Control Program (ARCP) - Eustachius Hagni Wardoyo; Didit Yudhanto; I Gede Yasa Asmara; Claresta Salsabila; Ajeng Retno (Rumah Sakit Penyakit Infeksi Prof Dr. Sulianti Saroso, 2020)
Background: A policy restricting the use of vancomycin was a pilot project for the implementation of the Antimicrobial Resistance Control Program (ARCP) in RSUD Nusa Tenggara Barat in 2018. There were three phases of the ARCP in hospitals, namely preparation, execution, and monitoring. This research aimed to evaluate the quality of vancomycin prescribing before, during, and after the implementation of ARCP in 2017–2019. Method: Descriptive analysis was conducted of all the vancomycin prescriptions before, during, and after the implementation of ARCP in 2018. All medical records of cases requiring vancomycin prescriptions during the research period was evaluated: patient characteristics, culture test results, and clinical diagnoses. The quality of vancomycin prescriptions, which was expressed as follows: “Vancomycin prescriptions are intended only for infections caused by Gram-positive pathogens, particularly Staphylococcus aureus, that are resistant to methicillin (MRSA), Enterococcus sp (Vancomycin-sensitive enterococci)” was evaluated. Results: There were sixty-one cases of vancomycin prescribing; 21 female and 40 male patients, with a mean age of 23 years (0–82 years). Overall, there were 41 positive cultures, 5 negative cultures, and 15 no-cultures. The diagnoses were moderate to severe infections: sepsis, pneumonia, post-surgery infections, CNS infections, low birth weight, septic shocks, and chronic obstructive lung diseases. The urinary tract infection was present as a mild infection. The prescription quality indicators ‘vancomycin is prescribed only for moderate to severe infections’ and ‘prescribed only for Gram-positive pathogens’ altogether increased. Conclusion: There was improvement in the vancomycin prescription quality after the implementation of the vancomycin restriction policy.